Monarchy Interactions in the International Political System: A Case Study of Royal Interactions between Kelantan and Thailand, 1979-2010 - Asmady Idris; Marja Azlima Omar; Rizal Zamani Idris (Iranian Association of Geopolitics, 2022)
This article examines the role of the monarchy institution by focussing on the Kelantan monarchy institution, especially during the reign of the Al-Marhum Kebawah Duli Yang Maha Mulia Tuanku Ismail Petra (1979-2010), which had shown noteworthy contributions in strengthening bilateral relation between two monarch families of Kelantan and Thailand. The study endeavours to analyse why the relations of these two monarch families are intimate, and how they are able to sustain their mutual interactions which benefits both royal institutions? In answering these two important questions, the study divides the scope of discussion into three main points. Firstly, it attempts to locate the position of the monarch institution in the international political system vis-à-vis the prevailing modern state system of government nowadays. Secondly, it explores the early interactions of the Kelantan and Thailand monarchs which sets the bedrock of the present relations. Thirdly, it assesses the role of Al-Marhum Kebawah Duli Yang Maha Mulia Sultan Ismail Petra as the main focus of the study, to sustain the relations with the Thai royals, and concurrently has benefitted both in developing the Royal Kelantan socio-development projects, and dealing with the crisis in the southern part of Thailand. The methods of this study comprised of interviews with the Kelantan monarch and its officials before and during the 2007 Royal Commemoration of Universiti Malaysia Sabah and content research of written documents from archives and library research.